EVALUASI KEBIJAKAN INSTALASI PENGELOLAAN AIR LIMBAH INDUSTRI BATIK DI KELURAHAN SIMBANGKULON KECAMATAN BUARAN, KABUPATEN PEKALONGAN - Laeli Lutfiawati; Dewi Erowati (Journal of Politic and Government Studies, 2026)
Environmental pollution caused by batik industrial waste has become a crucial issue in Pekalongan Regency, one of the major batik hubs. This condition reflects weaknesses in policy- based environmental management. Simbangkulon was selected by the Pekalongan Regency Government as the site for a communal Wastewater Treatment Plant (IPAL), which was expected to manage waste collectively. However, the facility has yet to resolve the ongoing pollution, raising questions regarding the effectiveness of policy implementation. This study aims to examine the gap between policy design and the reality of implementation at the local level. The theoretical framework used is William N. Dunn’s policy evaluation, which employs six criteria: effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. A descriptive qualitative approach was used, with data collection techniques including interviews, observations, and documentation. Research informants included government officials, IPAL managers, batik entrepreneurs, and the local community. The results indicate that the implementation of the IPAL policy in Simbangkulon is not yet optimal and tends toward systemic failure. This is characterized by persistent environmental pollution, limited IPAL capacity, and unequal access to the facility. Furthermore, low compliance among entrepreneurs is evident through their indifferent attitude toward waste management and refusal to pay service fees. A lack of regulatory understanding also leads to recurring violations. On the other hand, weak coordination between agencies has rendered the policy ineffective. These findings highlight a gap between normative policy and field implementation. This study concludes that the primary issue lies in weak implementation governance rather than a lack of policy. Therefore, strengthening regulatory enforcement, increasing entrepreneur awareness, and fostering more integrated institutional coordination are essential for the IPAL policy to operate optimally.